ANALYSIS OF BUSINESS SERVICE INNOVATION STRATEGIES ON SUSTAINABLE BUSINESS PERFORMANCE THROUGH THE “SIKOMPAK” APPLICATION (STUDY ON PERUMDAM TIRTA KENCANA REGION 1 SAMARINDA CITY) - Muhammad Naufal Azhari; Poppy Alvianolita Sanistasya; Fareis Althalets; Rosyid Nurrohman (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This study aims to analyze service innovation strategies through the “SiKompak” application in supporting sustainable business performance at PERUMDAM Tirta Kencana, Regional Service Unit 1, Samarinda City. The focus includes evaluating the application's usefulness in enhancing service delivery and identifying internal and external factors to formulate strategies that influence business sustainability. This research uses a descriptive qualitative approach with an interactive analysis model by Miles and Huberman, which involves data collection, reduction, presentation, and conclusion drawing. Data were obtained through in-depth interviews with five informants from various organizational levels, providing a comprehensive perspective on the application’s implementation. IFAS and EFAS analyses were conducted to develop the SWOT matrix. The findings show that SiKompak contributes positively to service effectiveness and employee performance. The application is operationally integrated, supported by adequate devices and relevant features, thereby improving efficiency, data accuracy, and response speed to customer complaints. From a sustainability perspective, SiKompak promotes economic efficiency, equitable workload distribution, and reduction of physical waste. However, technical challenges such as network disruptions and data synchronization still need to be addressed. The SWOT analysis places the innovation strategy of SiKompak in Quadrant II, recommending a defensive diversification strategy that focuses on strengthening internal capacity to address external challenges and ensure long-term sustainability. The novelty of this research lies in the integration of digital innovation strategies with a sustainability approach, as well as the use of a multi-level interview method within the organization.